Consequences of Weak Internal Controls Over Financial Reporting: Foreign versus U.S. Firms - Kathleen M Bakarich; Devon Baranek (Journal of Accounting, Business and Management (JABM), 2021)
For a sample of both foreign cross-listed firms and U.S. firms that report material weaknesses in internal control over financial reporting (MWICFR) from 2007- 2016, we utilize event studies and multivariate techniques to examine if there are differential consequences of reporting MWICFR across the two groups. Specifically, we examine the reactions of the equity and debt markets, external auditors, and the firm’s governance. We find that after receiving an audit report with material weakness issues, foreign firms face a significantly more negative stock market reaction and decrease in credit ratings. These firms are more likely to receive a going-concern audit opinion than U.S. firms and are also significantly less likely to change their CEOs or CFOs. Additionally, we find that the strength of the home market regulatory environment mitigates the negative equity and debt market reactions for foreign firms. Lastly, we also find that the presence of foreign auditors for foreign firms alleviates audit market consequences, resulting in a lower likelihood of auditor resignations and going-concern audit opinions. This paper extends and complements the existing literature on cross-listed firms by documenting differences in the consequences for firms reporting weaknesses in ICFR and exploring the traits driving these differences.